Lithuanian National Minority in Latvia (Late XIX Century–1940): The Role of Lithuanian Catholic Priests - Jekabsonas, Erikas (Lietuvos istorijos studijos, 2015)
Since the second half of the 19. century, Latvian industrial cities – Riga, Liepaja and Jelgava – became important centers of the Lithuanian social life, because they hosted numerous ethnical Lithuanian populations. They were Catholic by confession, with most of their members employed at the industrial enterprises and in other lower occupations. Part of them also lived in some small towns and rural parishes. After World War I, a significant part of Lithuanians migrated back to their ethnic homeland, However, there still remained a significant Lithuanian minority in the independent Latvia. Ethnically, Lithuanian Catholic priests did play a very significant role in the history not only of the Catholic Church, but also in that of the Lithuanian minority and of the Latvian state. In this broader context, their role was of special importance before 1918 when Lithuanian priests were active not only in the Lithuanian social movement in Riga and other places, but also did participate in the processes of the Latvian national revival in Latgale. Given the significance of a parish shepherd and his attitudes in the Catholic parishes at this time, their role was very important. Lithuanian Catholic priests did continue to play a major role in the maintenance and development of the system of culture, education, and social organizations of the Lithuanian minority also during the interwar time.
Keywords: Lithuanians ir Latvia; Lithuanian Catholic priests; Catholicism in Latvia; Latvian national revival in Latgale